2011
DOI: 10.1186/cc9976
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal life support following out-of-hospital refractory cardiac arrest

Abstract: Introduction: Extracorporeal life support (ECLS) has recently shown encouraging results in the resuscitation of inhospital (IH) refractory cardiac arrest. We assessed the use of ECLS following out-of-hospital (OH) refractory cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
155
3
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(172 citation statements)
references
References 37 publications
(64 reference statements)
3
155
3
11
Order By: Relevance
“…In contrast, the use of ECLS in the management of OHCA remains a matter of debate with survival rates ranging from 4 to 29% (13,14). Le Guen et al reported survival of 4%, with a median low-flow of 120 min, in a cohort of 51 patients with RCA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the use of ECLS in the management of OHCA remains a matter of debate with survival rates ranging from 4 to 29% (13,14). Le Guen et al reported survival of 4%, with a median low-flow of 120 min, in a cohort of 51 patients with RCA.…”
Section: Discussionmentioning
confidence: 99%
“…While there was some variability in time points of reported outcomes, the overall reported survival rate was 22%, including 13% having a good neurological recovery (CPC 1-2 or GOS 4-5, see Table 1). In addition to these short-term results, three studies 12,13,19 reported patient outcomes at 3 months with an overall survival rate of 21% (24/115), including 15% (17/115) having good neurological function and five studies 16,20,22,26,30 reported patient outcomes at 6 months with an overall survival rate of 16% (61/377), including 9% (34/377) having good neurological function.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included studies presented high risk of confounding bias and threats to external validity because of their observational design. However, the methodological quality assessment of the 20 included studies resulted in a rating of good for 14 studies [12][13][14][15][16]18,20,[22][23][24][25][26][27][28] and fair for the other 6 17,19,21,29-31 (see Table 1). …”
Section: Ecpr Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in patients with an out-of-hospital witnessed cardiac arrest who remain in refractory arrest, a single-center study reported extremely poor outcomes, even when ECMO was initiated very early (median time, 120 minutes), with only 4% of patients surviving to hospital discharge with a favorable neurological prognosis. 13 …”
Section: Clinical Evidencementioning
confidence: 99%